STATUS KEBERLANJUTAN PERIKANAN TANGKAP DI DAERAH KOTA PANTAI: PENELAAHAN KASUS DI KOTA MANADO (The Status of Sustainable Capture Fisheries in Coastal City Region: Case Study for Manado City) - Gybert E. Mamuaya; John Haluan; Sugeng H. Wisudo; I Wayan Astika (Institut Pertanian Bogor, 2007)
The capture offisheries sustainability is management and the utilization of fish resources which can guarantee the availability of that resources continuously. In this research, the sustainabili ty status offisheries in Manado city has been examined through ecological, economic, sociological, technological, and ethical approaches by employing RAPFISH technique. The status of the purse seine fishery in this region is 53% of the fisheries sustainability which is classified as good fisheries. Meanwhile, tuna long pole lines and gillnets fisheries status are 57.5% and 60.1 %, respectively, of the good fisheries sustainability. Improvement of this status can be carried out by improving the severalattributes qualities, among others: wage, other income and sector employment (economy); socialization offishing, environmental knowledge and kin participation (social); pre-sale processing, gear selectivity and fishing power (technology); alternatives and just management (ethics).Key words: sustainability, fisheries status, coastal city